Online Handwriting Recognition System - Voon , Choi Peng (UTeM, 2009)
Online Handwriting Recognition system (HWRS) is a software use to convert handwritten character into text format. This project highlights the development of online handwriting recognition system using Microsoft Visual Basic 6.0, Support Vector Machine (SVM) and, VBTablet 2.0 to recognize the input character by matching the prototypes. This may take place by writing directly on to a digitizing tablet by using stylus which is connected to the Universal Serial Bus (USB) port of a computer. Owing to the fact that each individual has its own way of presenting his/her handwriting on tablet, there is a certain level of complexity like the way of holding the stylus, the strokes use in the writing and the amount of time and pressure put on tablet which are involved in this recognition system. The general on-line recognition procedures are preprocessing, features extraction, coarse classification, detail matching and postprocessing. In this project the classifier used is the Support Vector Machine (SVM) and a new extractor is proposed consisting of time and pressure data, which provides of several more meaningful features of the handwritten character. The experiment results show that the SVM trained using features from time and pressure data makes the time and pressure technique interesting and competitive since the features has certain recognition advantages such as a convex objective function with very fast training algorithms.